Evidence for cerebellar motor functional reorganization in brain tumor patients: An fMRI study. (27th May 2016) - Kurabe, Satoshi; Itoh, Kosuke; Nakada, Tsutomu; Fujii, Yukihiko
Highlights: Cerebellar functional reorganization was studied in nonparetic brain tumor patients. Patients underwent a contralesional unilateral hand grasping task in fMRI. The primary sensorimotor activation was spatially displaced by the tumor. Contralesional cerebellar activation was increased compared to normal controls. Cerebellum contributes to motor functional reorganization in brain tumor patients. Abstract: Functional reorganization of the motor system following brain damage has been studied extensively in stroke patients, in which not only the cerebrum but also the cerebellum (Cbll) undergoes substantial reorganization. However, the role of Cbll in motor functional reorganization in brain tumor patients remains poorly investigated. Because brain damages in brain tumor patients occur much more slowly than in stroke patients, the neural mechanisms for motor functional reorganization might differ between these two disease conditions. This functional magnetic resonance imaging (fMRI) study investigated whether Cbll constitutes the neural substrates for motor functional reorganization in eighteen supratentorial brain tumor patients who exhibited no clinical signs of paresis. The patients and normal volunteers underwent a unilateral hand movement task. In the patients, the locus of primary sensory motor (SM1) activation during contralesional hand movement was significantly displaced by the tumor, suggesting functional compromise and/or reorganization in the central sulcus region. In addition, their contralesional Cbll activation during contralesional hand movement was substantially increased as compared to normal controls. The finding represents the first conclusive evidence that Cbll is involved in the motor-related functional reorganization in patients with brain tumor.